Degradación ambiental, agricultura y decisiones productivas. Un estudio de un área de la pampa argentina - Fernández, Guillermina; Guerrero, Marcela; Jacinto, Guillermina; Nogar, Graciela; Valenzuela, Silvia; Posada, Marcelo (Sociedade & Natureza, 2021)
Degradación ambiental, agricultura y decisiones productivas. Un estudio de un área de la pampa argentina